Wanita dan Kodrat Alamiahnya: Suatu Tinjauan Anthropologis Kedokteran - T. Jacob T. Jacob (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1980)
Commemorating the centennial of the birth of the reknown Indonesian feminist, R. A. Kartini, the author touched upon the discrimination against women and the achievement of the emancipation movement in the medical profession. The author then reviewed the natural vigour of the female sex, starting with the thesis of Greulich and sex dimorphism. Subsequently, sex ratio and sex differences in mortality, life expectancy and prevalence of various diseases are discussed. Growth disturbance and canalization are stressed upon to reveal the greater strength of the